Sinonimitas dalam Al-Qur’an: Lafadz Sanah dan ‘Am (Kajian Semantik) - Dyah Adila Perdana; Ummu Hanifah Syamsuhri (Tarling : Journal of Language Education, 2022)
The phenomenon of synonyms in the Qur'an has become a common topic of discussion. In this study, we examine the synonymy of the lafadz sanah and 'am which both mean the year. The data used is a verse of the Qur'an which contains lafadz sanah and 'am. The aim is to find out the meaning of lafadz sanah and 'am in the Qur'an and the relationship between the meanings of lafadz sanah and 'am through semantic analysis. The research methodology used in this research is library research with a qualitative approach. As for the results of the study, it was found that lafadz sanah was used to indicate a bad year/woeful, sad, lousy, sick and tired. While in lafadz 'am it is used to indicate the conditions of a happy, fertile and prosperous year. Then lafadz sanah and 'am are also analyzed based on semantic meaning according to Abdul Chaer who divides the types of meaning into 12, namely lexical meaning, grammatical meaning, contextual meaning, referential and non-referential meaning, denotative meaning, connotative meaning, conceptual meaning, associative meaning, word meaning. , the meaning of terms, the meaning of idioms, and the meaning of proverbs. As for the lafadz sanah and 'am in the Qur'an, several similar meanings are found and there are also some differences based on the semantic meaning according to Abdul Chaer.